The Suitability of the Components of the Daily Assessment Book for Junior High School IPA Teachers (Biology) in Bekasi - Adisti Ratnapuri; Fajar Adinugraha (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2023)
The Teacher's Daily Assessment Book is a form of teacher management. In fact, not all teachers are able to complete it. Therefore, the purpose of this study was to determine the format of the teacher's daily assessment book and to describe the suitability of the components of the daily assessment book in junior high school science teachers (biology). The research method used was field research with observation and interview techniques. The informants in the study were 10 junior high school science teachers (Biology) in Kecamatan Rawalumbu, Bekasi. All the respondents (100%) have document completeness in books 1 and 4. Unfortunately, not all the respondents have document completeness in books 2 and 3. Looking at the document completeness in book 2, only 50% of the respondents have document completeness. In Book 3, none of the respondents had 100% document completeness. The range of document completeness was from 69.23% to 84.62%. Finally, not all teachers have 100% complete documents in the workbook. This may be due to the administrative burden. This research is expected to provide insight into the need to balance the quality of teaching and the administrative burden on teachers.